Internal Structures and Growth Style of a Quaternary Subaerial Rhyodacite Cryptodome at Ogariyama, Usu Volcano, Hokkaido, Japan - Goto, Yoshihiko; Tomiya, Akihiko (Frontiers in Earth Science, 2019)
Cryptodomes are shallow-level intrusions that cause updoming of overlying sediments or other rocks. Understanding the formation of cryptodomes is important for hazard assessment, as cryptodome-forming eruptions are one of the major triggering factors in sector collapse. This paper describes internal structures of a Quaternary subaerial rhyodacite cryptodome at Ogariyama, Usu volcano, Japan (the Ogariyama dome), and examines the textural differences between subaerial and subaqueous cryptodomes to extend our knowledge of these phenomenon. The Ogariyama dome, which is one of the youngest subaerial cryptodomes in the world (<0.4 ka), can be viewed in cross-section because a vertical fault formed during the 1977–1978 eruption and cut through the center of the cryptodome, exposing its interior. The morphology of the cryptodome is scalene triangular in shape, with rounded corners in cross-section, and it is 150 m across and 80 m high. The internal structure of the dome is concentrically zoned, with a massive core, jointed rim, and brecciated border, all of which are composed of uniform, feldspar-phyric rhyodacite (SiO2 = 71–72 wt.%). The massive core (130 m across) consists of coherent rhyodacite that has indistinct, large-scale flow banding and rectangular joints that are spaced 50–200 cm apart. The jointed rim (8–12 m wide) surrounds the massive core and consists of coherent rhyodacite that is characterized by distinct rectangular joints that are 30–80 cm apart and radiate outward. The outermost brecciated border (7–10 m wide) comprises monolithological breccia, consisting of angular rhyodacite clasts (5–30 cm across) and a cogenetic matrix. These internal structures suggest that the Ogariyama dome was formed by endogenous growth, involving continuous magma supply during a single intrusive event and simple expansion from its interior. The massive core formed by slow cooling of homogeneous rhyodacite magma. The jointed rim formed by fracturing of solidifying rhyodacite magma in response to cooling–contraction and dynamic stress driven by continued movement of the less viscous core. The brecciated border formed by fragmentation of the solidified rim of the dome in response to dynamic stress. The growth style of the Ogariyama dome closely resembles that of subaqueous cryptodomes. However, the morphology and internal structures of the Ogariyama dome differ from those of subaqueous cryptodomes, given its asymmetric morphology and absence of radial columnar joints and large-scale flow banding. These differences might reflect the well-consolidated and inhomogeneous physical properties of the host sediment and the slow cooling rate and high viscosity of the Ogariyama dome. The Ogariyama dome is probably the best cross-sectional example of a subaerial cryptodome in the world. Our descriptive study of the cryptodome provides invaluable information for hazard assessment.